Between algorithms and editorial routines: Trust in the UN and European public opinion - Sousa, J. C. (Texto Livre: Linguagem e Tecnologia, 2026)
This research analyzes the determinants of European public opinion trust in the UN in the context of war and informational disorder. It proposes a model that integrates three dimensions: informational, heuristic, and identity/polarizing, and an institutional indicator: perception of press freedom. The analysis is based on data from Eurobarometer 98.2 and uses PCA and binary logistic regression. The results indicate that trust in the media is the most robust predictor, confirming the importance of credibility heuristics. Radio and press usage have small but consistent effects, while digital media reveal an ambivalent and statistically null impact. Participation in online political debates is positively associated with trust, as well as with the perception of press freedom. The study highlights the link between public opinion, media, and institutional trust, offering guidelines for policies on informational integrity and media literacy.